Second sight secrets and mechanical magic - Pinetti, Herman (Salt Lake City, UT : Project Gutenberg, 2025)
"Second Sight Secrets and Mechanical Magic" by Dr. Herman Pinetti is a practical guide to the art of mechanical magic and illusions, written in the early 20th century. The book serves as a manual for aspiring magicians and those intrigued by stage performances, detailing the secrets behind various tricks that create the illusion of spiritualism and mind-reading. The author aims to debunk the notion that these performances rely on the paranormal, showing instead that they are achieved through clever mechanics and psychological techniques. The content of the book is structured around different types of magical tricks, from cabinet illusions to table lifting, and features detailed explanations of how they are executed. Dr. Pinetti breaks down the mechanics behind popular effects such as "Second Sight," where one participant, often blindfolded, accurately guesses information about items held by audience members. He explains various methods involving props, theatrical setup, and psychological manipulation that professional performers use to create a sense of wonder. Throughout the text, Pinetti combines historical anecdotes with hands-on instructions, making the book both educational and entertaining for those interested in the art of illusion. (This is an automatically generated summary.)
Release date is 2025-01-01
Bob Taylor, deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Magic tricks